Pelatihan Optimalisasi Pemasaran Produk UMKM melalui Sosial Media Tiktok - Btari Mariska Purwaamijaya; Oding Herdiana; Syti Sarah Maesaroh; Rangga Gelar Guntara (Insan Kreasi Media, 2022)
Digital marketing has many advantages over traditional marketing. With digital marketing, business actors and potential consumers do not need to always meet face to face. This is certainly a very good thing, especially in the midst of the dangers of the current pandemic. In addition, marketing in the digital world has a very wide reach without being limited by space and time. So that the wider the marketing reach, the wider the opportunity to reach potential consumers. One type of digital marketing that is currently becoming a trend is marketing on social media. There are so many social media that can be used for marketing. One of them is Tiktok social media. training activities for optimizing the marketing of MSME products through social media Tiktok have been running smoothly. participants can already make marketing videos on Tiktok. The output of this research is in the form of articles published in national journals.